Subsidence Control Design Method and Application to Backfill-Strip Mining Technology - Xiaojun Zhu; Feng Zha; Guangli Guo; Pengfei Zhang; Hua Cheng; Hui Liu; Xiaoyu Yang (Advances in Civil Engineering)
Intensive and massive coal mining causes a series of geological hazards and environmental problems, especially surface subsidence. At present, two major types of subsidence control technology are applied: backfilling technology and partial mining technology. However, the cost of backfill mining is high and partial mining has a low recovery ratio. Therefore, the backfill-strip mining is used to solve the problems of high cost and shortage of filling materials in coal mines at present. A subsidence control design method of backfill-strip mining was proposed in this paper based on the subsidence control effects and economic benefits. First, the stability of the composite support pillar of the filling body and coal pillars in the backfill-strip mining is analyzed, and the values of the main subsidence influencing factors that include the filling material, the size of the backfilling working face, caving mining face, and residual coal pillar are preliminarily determined. Then, the surface movement and deformation are predicted based on the equivalent superposition probability integral method (PIM). The subsidence influencing factors are optimized and determined by comparing the requirements of the safety fortification index of the antideformation ability of surface buildings, resource recovery rate, and coal mining cost. Finally, the mining scheme design parameters of the backfill-strip mining technology are determined. This method is applied in the subsidence control design of backfill-strip mining in the Ezhuang coal mine. Research results show that backfill-strip mining can ensure the safety of surface buildings, increase the resource recovery rate, and reduce coal mining costs through the reasonable design of this method. This study can provide scientific guidance for subsidence disaster control, prevention, and engineering design in backfill-strip mining.